Formal Methods for Industrial Critical Systems: 20th International Workshop, FMICS 2015 Oslo, Norway, June 22-23, 2015 Proceedings - Núñez, Manuel (Springer, 2015)
This book constitutes the proceedings of the 20th International Workshop on Formal Methods for Industrial Critical Systems, FMICS 2015, Oslo, Norway, in June 2015.